PERKEMBANGAN INFRASTRUKTUR DAN PERUBAHAN HIRARKI KOTA (STUDI KASUS KABUPATEN/KOTA DI JAWA TENGAH BERDASAR TAHUN SENSUS PENDUDUK 1990, 2000, 2010) - Matitaputty, Shandy Jannifer; Primadani, Anita (Fakultas Ekonomi dan Bisnis Universitas Ahmad Dahlan, 2017)
The population growth of a region and its adjacent areas will create new needs. These needs are created by the advancement of culture and the increasing complexity of population activity. The emerging needs give rise to the consequent increase in infrastructure provision. The availability of adequate municipal infrastructure is believed to be one of the factors driving the cityâs development as reflected in the hierarchy of the city.Central Java province has 35 districts adjacent and interact with each other.Each of these districts has a population that changes with time. City residents are considered as a society that has high economic activity that will spur revenue growth region.The development of urban infrastructure is likely to result in the development of the urban population which ultimately increases the hierarchy of the city. This study intends to see whether infrastructure developments in districts in Central Java will result in an increase in urban population in the region which further impacts on changes in the hierarchy of cities. The results show that population growth has resultedin increased population activity, transportation and technology systems along with the times. In the long run, this leads to a change of urban hierarchy. This is also because the adjacent districts will be connected and infl uenced. Changes in the hierarchy of cities that occurred in the years 1990-2010 in the district in Central Java province showed that the highest hierarchy position occupied by Semarang City. This is driven by the rapid development of infrastructure and technology in Semarang City. The rapiddevelopment of infrastructure and technology of Semarang City become a big enough attraction for residents of the surrounding area to move to Semarang City